Analysis of Nursing Clinical Practice with Chest Physiotherapy Innovation Intervention and Pronation Position on Airway Clearance in Pediatric Patients with Pneumonia in The Keruing Room - Sriwidiastuti, Elysa; Prasetyana, Ely; Krisneki, Ice; Kartini, Kartini; Bulan, Magdalena; Rahman, Gajali; Andraini, Rus; Mari’pi, Farida (Rifa'Institute, 2023)
Introduction: Pneumonia is also known as